1993
DOI: 10.1128/iai.61.6.2347-2356.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and immunolocalization of a Cryptosporidium protein containing repeated amino acid motifs

Abstract: The oocyst wall is one of the components that permits cryptosporidia both to survive in the environment and to retain infectivity. With the aim of identifying Cryptosporidium proteins specifically expressed at the oocyst stage, we screened Agtll genomic libraries of Cryptosporidium parvum with both an oocyst antiserum and a * Corresponding author.We thought that such genes would be important both in understanding how the parasites survive and retain infectivity for several months in the external environment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…4b are consistent with an ionic bridging binding process that arises due to EDL events (10,11,14,45,46); however, the magnitude of the force indicates that various surface characteristics of the oocysts may contribute to these interactions (11,12). The C. parvum wall structure has been reported to be multilayered, with the outer layer of the wall covered in acidic glycoproteins (6,54,55); the outer-wall structure exhibits an isoelectric point of ϳ2.5, thus exhibiting a negative charge at the experimental pH of 6.8. In addition, this outer wall possesses a glucose-rich glycocalyx, which likely plays a role in nonspecific physiochemical binding.…”
Section: Resultssupporting
confidence: 53%
“…4b are consistent with an ionic bridging binding process that arises due to EDL events (10,11,14,45,46); however, the magnitude of the force indicates that various surface characteristics of the oocysts may contribute to these interactions (11,12). The C. parvum wall structure has been reported to be multilayered, with the outer layer of the wall covered in acidic glycoproteins (6,54,55); the outer-wall structure exhibits an isoelectric point of ϳ2.5, thus exhibiting a negative charge at the experimental pH of 6.8. In addition, this outer wall possesses a glucose-rich glycocalyx, which likely plays a role in nonspecific physiochemical binding.…”
Section: Resultssupporting
confidence: 53%
“…Ranucci et al (33) cloned a DNA fragment encoding an oocyst protein (COWP-190) of C. parvum. The first 2,359 bp of their clone was identical to the DNA sequence reported by Lally et al (22).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of Cryptosporidium organisms by PCR required a nested step since the primers published by Ranucci et al (20) for the 753-bp amplicon resulted in nonspecific amplification, as evidenced by the numerous nontarget bands in Fig. 1a, and did not allow visualization of the target 753-bp band.…”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, the sewage samples were analyzed for Giardia and Cryptosporidium organisms by PCR. Primers reported by Mahbubani et al (12) were used for Giardia detection while a nested PCR based on primers reported by Ranucci et al (20) was developed for Cryptosporidium detection.…”
mentioning
confidence: 99%